PENERAPAN ACTIVE LEARNING UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR APRESIASI MUSIK NUSANTARA PADA SISWA KELAS VIII A SMP NEGERI 7 PEMALANG - Martini, Ida (Universitas Negeri Semarang, 2014)
This study examines the implementation of active learning strategy by using Have Student Question type, aiming to increase students interest and appreciation towards national music, especially on the basis of national competence. The approach used for the research , which is implemented with two cycles, and each cycle consists of four stages: planning, action, observation, and reflection. The research was conducted in Pemalang Junior High School 7. The data collection techniques used in this research was quantitative and qualitative data which includes the test results of students learning, the observation of students and the implementation of the learning process, as well as students interest questionnaire. The results shows significant increase in interest and appreciation of national music learning outcomes in the eighth grade students of Pemalang Junior High School 7, academic year of 2012-2013. This is proven from the results of student learning on the pre cycle which was only 37.5%, then increased to 65% on the first cycle, and finally reached 82.5% on the second cycle. The improvement was highly visible, from 10% on the pre cycle, 50% on the first cycle, and 80% on the second cycle .To improve students learning outcomes and students interest in learning, the teachers need to prepare in advance: ( a) Lesson Plan, (b) learning materials, (c) the methods or strategies that will be used, (d) tools or instructional media, (e) control of classroom management, (f) evaluation sheet.